Environmentally Friendly Biosorbent from Moringa Oleifera Leaves for Water Treatment - Ali, Eman N.; Alfarra, Sabreen R.; M. M., Yusoff; Lutfor, M. R. (IACSIT Press, 2015)
In this study Moringa oleifera leaves (biosorbent) is used for Cadmium (II) removal from water as a natural alternative for synthetic sorbents. Synthetic water was used to find optimum conditions for water treatment using biosorbent. The effect of biosorbent dosage and particle size, contact time, and pH effect were studied. Atomic Absorption Spectroscopy (AAS) was used to monitor the Cd (II) concentration before and after treatment with biosorbent. Fourier Transform Infrared Spectroscopy (FTIR) was used to monitor biosorbent structure changes before and after loading with Cd (II). Many parameters were studied such as: dosage of biosorbent (1 – 10 g/L), contact time (2 – 20 min), particle size (2 mm, 1 mm, 500 µm, 250 µm, and <250 µm), pH range (4-10), and Cd (II) concentrations (1, 3, 5, and 7 ppm). The statistical analysis of studied parameters showed that all parameters has an effect on Cd (II) removal with p values <0.05 except pH. FTIR result showed changes in the finger print area of biosorbent functional groups due to adsorption of Cd (II). As a conclusion, Moringa oleifera leaves can be used as an effective, low cost, and environmentally friendly biosorbent for the removal of Cd (II) from water.